Wide entrance and tall windows in the reception hall - Mumbai Archive Project (Jio Institute, 2024)
The wide entrance and tall windows along the reception hall keep the interiors breezy and well-ventilated. The reception hall—the largest room in the club—is naturally illuminated by sunlight during the day. The building is west-facing, and light streaming in the late afternoon casts long shadows in the reception hall.